Application Study on Building Information Model (BIM) Standardization of Chinese Engineering Breakdown Structure (EBS) Coding in Life Cycle Management Processes - Liye Zhang; Lijuan Dong (Advances in Civil Engineering)
The successful adoption of building information modelling (BIM) technology has led to an ever-increasing need for improving management practices in both construction and operation stages of highway project engineering. The most significant aspect of applying BIM technology is establishing the rationality and concise engineering breakdown structure (EBS) coding. However, China has no uniform EBS coding standard for highways, which limits BIM technology development in different construction projects and at different stages of the same construction project. The purpose of this study is to propose an EBS standard that embodies a coding system for highways and at the same time meets the requirements of BIM management, project management (PM), and operation management (OM) in life cycle management process. This paper presents an EBS standard based on three classifications: (1) project-level construction, (2) project-level operation, and (3) network-level operation. A case study is given to illustrate the proposed EBS standard’s coding system. The new EBS system will have better adaptability in both the design and construction stages. The proposed EBS coding system has been applied in many projects and is undergoing both improvement and standardization in China. The presented EBS coding standard provides successful implementation references for the future adoption and use of BIM on PM and OM in highway projects.